2016
DOI: 10.5812/pedinfect.37968
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Extended-Spectrum β-Lactamase Genes and AmpC-β-Lactamase in Clinical Isolates of Escherichia coli Recovered from Patients with Urinary Tract Infections in Kerman, Iran

Abstract: Background: Escherichia coli is the main causative pathogen in urinary tract infections (UTIs). Antibiotic resistance in this bacterium is an important problem in public health. Objectives: The aim of this study was to identify the blaTEM, blaSHV, blaOXA, and blaPER genes and AmpC-β-lactamase in clinical isolates of E. coli recovered from patients with UTIs in Kerman, Iran. Methods: E. coli isolates (N = 105) were analyzed for their antibiotic susceptibility with the disk diffusion method. ESBL and AmpCproduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 30 publications
7
17
2
Order By: Relevance
“…Findings are in line with the earlier studies in Iran [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The findings of previous studies as well our current findings indicate that ESBL and AmpC-β-lactamase-producing isolates are typically resistant to others antibiotics such as trimethoprim/sulfamethoxazole and fluoroquinolones [13]. ESBL was detected in 41/105 (43%) of the isolates recovered from patients, and bla CTXM was the commonest genotype (93%).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Findings are in line with the earlier studies in Iran [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The findings of previous studies as well our current findings indicate that ESBL and AmpC-β-lactamase-producing isolates are typically resistant to others antibiotics such as trimethoprim/sulfamethoxazole and fluoroquinolones [13]. ESBL was detected in 41/105 (43%) of the isolates recovered from patients, and bla CTXM was the commonest genotype (93%).…”
Section: Discussionsupporting
confidence: 93%
“…Klebsiella pneumonia ATCC 700603 and E. coli ATCC 25922 were used as positive and negative controls respectively. Furthermore, AmpC phenotype was specified by means of compound disk using cefoxitin (FOX), (Mast, UK) with and without boronic acid (Sigma-Aldrich Chemie, , Germany) were used to detect AmpC phenotypes [13].…”
Section: Detection Of Esbls and Ampc-positive Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of samples collected are donated to all patients included in the study and some sample results were dispatched to physicians for treatment prescription [47][48][49].…”
Section: Resultsmentioning
confidence: 99%
“…Chih et al, in a study about nephropathy in infants with urinary tract infection, evaluated 152 young infants (127 males and 25 females) and concluded that E. coli was the most common pathogen in urinary tract infection and had high ampicillin resistance, and leukocytosis indicated the risk of VUR while fever indicated a risk of pyelonephritis (18). Koshesh et al, in their study, evaluated ESBL E. coli infections and they found that these isolates were higher in communities rather than inpatients (19). Rahman et al in a case -control study reported male gender and high grade reflux as risk factors of nephropathy among children with UTI; also, the current study demonstrated that reflux was seen as a risk factor for urinary tract infections (7).…”
Section: Discussionmentioning
confidence: 81%